Prevalence protilátek proti viru hepatitidy E v České republice - sérologický přehled - Němeček, V; Butovičová, P; Malý, M; Dítě, P; Veřtátová, M; Vodičková, I; Kříž, B (Epidemiologie, mikrobiologie, imunologie, 2017)
AIM: To determine the prevalence of antibodies against hepatitis E virus in the general population of the Czech Republic of age 15 to 64, to analyse the age and sex distribution of these antibodies, and to evaluate the benefit of the immunoblot test for the confirmation of the specificity of the enzyme immunoassay (EIA) screening test. MATERIAL AND METHODS: Sera from the last available multipurpose serological survey conducted in 2001 were tested. Anti-HEV IgG was detected by the RecomWell HEV IgG EIA test (Mikrogen Diagnostik, Germany). The immunoblot assay RecomLine HEV IgG/IgM (Mikrogen Diagnostik, Germany) was used for confirmation. RESULTS: Using the RecomWell IgG EIA test, anti-HEV IgG reactivity was found in 115 (6.7%) of 1715 sera. No significant difference in the anti-HEV IgG reactivity was found between men 58 (6.9%) and women 57 (6.6%). The prevalence of anti-HEV IgG increased with age from 3.5% in the age group 15-24 years to 16.8% in 55-64-year-olds. CONCLUSIONS: The prevalence of hepatitis E IgG antibodies determined in the serological survey in the age group 15-64 years was 6.7%. Recalculated for the general population of the Czech Republic, the prevalence was 8.6%. The prevalence of anti-HEV antibodies increased with age, reaching a peak of 16.8% in the age group 55-64 years. The prevalence was not significantly different between men and women. Using the immunoblot RecomLine IgG test for the confirmation of the specificity of the screening test in the seroprevalence study was not of clear benefit.
Keywords: Prevalence; imunoglobulin G; mladiství; Česká republika; Middle Aged; Hepatitis E; mužské pohlaví; prevalence; Immunoglobulin M; Antibodies, Viral; Adult; mladý dospělý; Czech Republic; hepatitida E; imunoglobulin M; Hepatitis E virus; Immunoglobulin G; Young Adult; ženské pohlaví; Humans; hepatitis E virus - anti-HEV - prevalence - EIA - immunoblot.; Seroepidemiologic Studies; protilátky virové; lidé středního věku; séroepidemiologické studie; virus hepatitidy E; dospělí; Female; Adolescent; lidé; Male